2020
DOI: 10.3390/ijerph17176311
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Temporomandibular Disorder and Sleep Apnea—A Nationwide Population-Based Cohort Study

Abstract: An increased incidence of temporomandibular disorders (TMD) among patients with sleep apnea (SA) has been reported. However, the association between TMD and SA has not been demonstrated in a large-scale study. This population-based cohort study with the Taiwan National Health Insurance (NHI) Research Database aimed to understand the association between SA and TMD. We identified adult patients with suspected SA (identified with diagnostic codes) and excluded those diagnosed with TMD prior to SA. Patients with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…These symptoms have been previously shown to be coexistent. [ 4 5 , 10 22 ] In the present study, the k -medoids algorithm partitioned the participants into five distinct clusters, confirming the associations among such symptoms.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These symptoms have been previously shown to be coexistent. [ 4 5 , 10 22 ] In the present study, the k -medoids algorithm partitioned the participants into five distinct clusters, confirming the associations among such symptoms.…”
Section: Discussionsupporting
confidence: 72%
“…This is in accord with findings from a large cohort study showing that poor sleep quality preceded pain. [ 22 ] It has been suggested that sleep apnea is associated with a cascade of events involving sleep deprivation, intermittent hypoxia, and generation of inflammatory mediators, resulting in pain hypersensitivity. [ 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies focus on the influence of bruxism as a contributing factor to TMD pain aggravation 52 and more recently have investigated the relationship between TMD and sleep-related breathing disorders as a single disease entity stating obstructive sleep apnea as a risk factor of developing TMD. 53 , 54 The only other primary sleep disorder to be analyzed in relation to TMD is insomnia although the existing literature is scarce in spite of the fact that insomnia disorder is the most frequently diagnosed sleep disorder in TMD patients. 29 One study reported that insomnia was associated with reduced mechanical and thermal pain thresholds in myofascial TMD patients 29 and another study showed that the increases in insomnia symptoms were succeeded by increases in average daily TMD pain in the next month.…”
Section: Discussionmentioning
confidence: 99%
“…There is a limit to the extended interpretation of the results of the sleep quality and high risk of OSA in patients with chronic TMD, as the relationship between OSA and TMD. Of course, a bidirectional association between OSA and TMD have been suggested 24,54 . Although the clear mechanism has not been identi ed, oral appliances used in the treatment of OSA may be the cause of TMD with continuous mandibular advancement while sleeping 55 .…”
Section: Discussionmentioning
confidence: 99%